2022
DOI: 10.3389/fimmu.2022.986893
|View full text |Cite
|
Sign up to set email alerts
|

Anticardiolipin and/or anti-β2-glycoprotein-I antibodies are associated with adverse IVF outcomes

Abstract: ObjectiveThe purpose of the study is to evaluate the effects of anticardiolipin (aCL) and/or anti-β2-glycoprotein-I (aβ2GPI) antibodies, namely antiphospholipid antibodies (aPL), on in vitro fertilization (IVF) outcomes.Materials and methodsThe study group comprised infertile women with aPL undergoing IVF-ET cycles. Controls were infertile women with tubal etiology without aPL. The impact of aPL on reproductive outcomes, such as oocyte quality, embryo quality, and implantation capacity, was compared between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Recent studies have demonstrated that an imbalance in Th1/Th2 immune cells plays a crucial role in the pathogenesis of SCH. Cytokines produced by Th1 cells mainly mediate cellular immunity and inflammatory responses that can inhibit embryo implantation, trophoblast growth, embryonic development and fetal survival ( 14 , 15 ). Cytokines secreted by Th2 cells mainly mediate humoral immunity, which maintains pregnancy and antagonizes Th1 type cytokines.…”
Section: Etiology Of Schmentioning
confidence: 99%
“…Recent studies have demonstrated that an imbalance in Th1/Th2 immune cells plays a crucial role in the pathogenesis of SCH. Cytokines produced by Th1 cells mainly mediate cellular immunity and inflammatory responses that can inhibit embryo implantation, trophoblast growth, embryonic development and fetal survival ( 14 , 15 ). Cytokines secreted by Th2 cells mainly mediate humoral immunity, which maintains pregnancy and antagonizes Th1 type cytokines.…”
Section: Etiology Of Schmentioning
confidence: 99%
“…14 aPL might contribute to the process of conception, leading to idiopathic infertility. 65 Nevertheless, aCL and/or aβ2GPI might be associated with adverse in vitro fertilization (IVF) outcomes, 66 with the contribution of platelet-activating factor (PAF). 67 Multiple proposed explanations exist for implantation failure in APS.…”
Section: Female Ovariesmentioning
confidence: 99%
“…In this case, autoantibodies can be tested. This includes anti-cardiolipin antibodies, lupus anticoagulants, anti-β2-glykoprotein-I antibodies, anti-transglutaminase IgA, and anti-nuclear antibodies, which can be tested [ 199 , 201 ].…”
Section: Clinical Significance In Reproductive Medicinementioning
confidence: 99%